O Parque tecnológico de Sorocaba: governança e dinâmica socioprodutiva local - Hori, Ivana Iyulka [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Sorocaba is an important city from São Paulo‟s countryside which stands out for the industrial production and the recognition as the seat of government of a large administrative region of São Paulo. From the analysis of Sorocaba development intends to understand the territorial formation of Sorocaba Park Technological Alexandre Beldi Netto (SPT) investigating issues about the socioeconomic and institutional elements in order to characterize all the dynamics and articulations built up its consolidation, concomitantly, the analysis, municipal and state, at public policies implemented. We intend to study the evolution of the industrial city, identifying the emergence of material and immaterial (cultural/social) resources able to attract a project as a Technology Park. Accordingly, the social actors and the governance structure of the SPT appear as determinants an initial understanding about the impacts caused by this project to Sorocaba society. For this, we used the feature interview with the most important territorial actors, besides the constant research literature and secondary data collection (IBGE, RAIS SEADE etc) to achieve the desired results the light of the objectives and research hypotheses

Sorocaba é uma importante cidade do interior paulista que se destaca pela sua produção industrial e sua condição como sede de governo de uma grande região administrativa do Estado de São Paulo. A partir da análise do desenvolvimento do município, busca-se compreender a constituição territorial do Parque tecnológico de Sorocaba Alexandre Beldi Netto (PTS), investigando seus principais elementos socioeconômicos e institucionais a fim de caracterizar as dinâmicas e as articulações construídas até a sua consolidação, concomitantemente à análise das políticas públicas implantadas no âmbito municipal e estadual. Pretende-se assim, estudar a evolução industrial do município, identificando o surgimento dos recursos materiais e imateriais (cultural/social) capazes de atrair um projeto como o de um Parque Tecnológico. Nesse sentido, os atores sociais e a estrutura da governança do PTS aparecem como fatores determinantes para o entendimento das relações de poder e dos impactos ocasionados por este empreendimento à sociedade Sorocaba. Para tanto, foi utilizado o recurso de entrevista com os principais atores territoriais, além da constante pesquisa bibliográfica e coleta de dados secundários (IBGE, RAIS, SEADE etc) para consecução dos resultados pretendidos à luz dos objetivos e hipóteses de pesquisa
Keywords: Governança; Indústrias; Sorocaba (SP)